Smartphone Health Assessment for Relapse Prevention (SHARP): a digital solution toward global mental health - Elena Rodriguez-Villa; Urvakhsh Meherwan Mehta; John Naslund; Deepak Tugnawat; Snehil Gupta; Jagadisha Thirtalli; Anant Bhan; Vikram Patel; Prabhat Kumar Chand; Abhijit Rozatkar; Matcheri Keshavan; John Torous (BJPsych Open, 2021)
Background Predicting and preventing relapse presents a crucial opportunity and first step to improve outcomes and reduce the care gap for persons living with schizophrenia. Using commercially available smartphones and smartwatches, technology now affords opportunities to capture real-time and longitudinal profiles of patients’ symptoms, cognition, physiology and social patterns. This novel data makes it possible to explore relationships between behaviours, physiology and symptoms, which may yield personalised relapse signals.